Guyana : government policy orientation ([Government of Guyana] GeorgetownUS, 1994)
Provides an orientation to the Guyana government's policies and strategies for development. Looks at the government's policies for providing sound macroeconomic management and promoting private sector development; its programme of public sector reform and privatization; its priorities, policies and strategies in the real sector; its policies to improve the physical and social infrastructure; poverty alleviation and reduction; debt relief and mobilization of savings; and, implications for the donors and government.
DC